Guinea-Bissau : Request for a Nine-Month Staff Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Guinea-Bissau is a fragile state with considerable needs to fight the COVID-19 pandemic and address developmental challenges. After an estimated 1.4 percent of GDP contraction in 2020, a modest recovery of about 3.3 percent is projected for 2021 on the back of higher cashew exports, the gradual lifting of COVID containment measures and a more stable political situation. The outlook is subject to considerable uncertainty. An RCF disbursement of SDR 14.2 million (50 percent of quota) was approved in January to provide urgent financing (35 percent of the external gap in 2021) to support critical spending in health and catalyze additional donor resources. The RCF followed two years of protracted political turmoil and delays in reforms, now undertaken by the new government. Public debt was assessed as sustainable in a forward-looking sense based on the authorities' commitment to sound policies supported by strong donor engagement and a Fund program. Debt service relief under the CCRT has provided some fiscal space and the country's participation in the DSSI should also help mobilize additional resources. After the 2021 budget approval within the statutory deadlines, significant and sustained reform efforts are required to meet the WAEMU 3 percent of GDP overall balance criteria by 2025 and bring public debt-to-GDP ratio within 70 percent by end-2026.